Influence of carbon and nitrogen concentration on itaconic acid production by the smut fungus Ustilago maydis. Issue 2 (6th January 2014) - Maassen, Nicole; Panakova, Monika; Wierckx, Nick; Geiser, Elena; Zimmermann, Martin; Bölker, Michael; Klinner, Ulrich; Blank, Lars Mathias
<x xml:space="preserve">Abstract</x> Itaconic acid is a valuable platform compound for the production of bio‐based polymers, chemicals, and fuels. Ustilago maydis is a promising host for the production of itaconic acid from biomass‐derived substrates due to its unicellular growth pattern and its potential to utilize biomass‐derived sugar monomers and polymers. The potential of U. maydis for industrial itaconate production was assessed in pH‐controlled batch fermentations with varying medium compositions. Using 200 g/L glucose and 75 mM ammonium, 44.5 g/L of itaconate was produced at a maximum rate of 0.74 g L−1 h−1. By decreasing the substrate concentrations to 50 g/L glucose and 30 mM ammonium, a yield of 0.34 g/g (47 mol%) could be achieved. Itaconate production from xylose was also feasible. These results indicate that high itaconic acid titers can be achieved with U. maydis. However, further optimization of the biocatalyst itself through metabolic engineering is still needed in order to achieve an economically feasible process, which can be used to advance the development of a bio‐based economy.